Video Cartoons and Task-Induced Involvement: Effects to Pupils’ L2 Incidental Literacy Acquisition - Arabiana, Elaiza Flor S.; Malifer, Dayvin Adrian Ember A.; Betonio, Helen Ranoco (Universitas Ahmad Dahlan, 2020)
While most studies that explored children’s incidental literacy acquisition focused on input from written text, this quantitative-qualitative study investigated the effects of using audio-visual input through close-captioned Aesop’s Fables cartoons from PinkFong and Task-Induced Involvement (n=6 eight-year old pupils). Wilcoxon Signed Rank Test reveals that there is a significant difference in the pretest, immediate posttest and delayed posttests scores after the intervention as shown in the 90%-95% confidence level. This study also examines quantitatively the interconnectedness of the four areas of children’s literacy skills: vocabulary, oral vocabulary and pronunciation, orthographic skill and comprehension after watching cartoons and engaging in tasks. Findings reveal a high correlation between the four literacy skills reflected as 95% confidence intervals. These findings reveal that incidental literacy acquisition is approached holistictically: the acquisition of one skill leads to the acquisition of the other literacy skills.